2012
DOI: 10.1007/s10404-012-1024-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of size, shape and vessel geometry on nanoparticle distribution

Abstract: Nanoparticles (NPs) are emerging as promising carrier platforms for targeted drug delivery and imaging probes. To evaluate the delivery efficiency, it is important to predict the distribution of NPs within blood vessels. NP size, shape and vessel geometry are believed to influence its biodistribution in circulation. Whereas, the effect of size on nanoparticle distribution has been extensively studied, little is known about the shape and vessel geometry effect. This paper describes a computational model for NP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 52 publications
5
129
0
Order By: Relevance
“…This is in agreement with the findings from adhesion studies (3,(11)(12)(13)(14)17,18), as well as a recent direct-particle-tracking study by D'Apolito et al (7) in which two spherical particle sizes (1 mm and 3 mm) were investigated. It is conjectured that larger particles interact more readily with RBCs and, as a result of their frequent collisions with RBCs, are propelled toward the walls of a blood vessel sooner than smaller particles, which have less frequent interactions.…”
Section: Effect Of Particle Sizesupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with the findings from adhesion studies (3,(11)(12)(13)(14)17,18), as well as a recent direct-particle-tracking study by D'Apolito et al (7) in which two spherical particle sizes (1 mm and 3 mm) were investigated. It is conjectured that larger particles interact more readily with RBCs and, as a result of their frequent collisions with RBCs, are propelled toward the walls of a blood vessel sooner than smaller particles, which have less frequent interactions.…”
Section: Effect Of Particle Sizesupporting
confidence: 91%
“…This so-called enhanced permeability and retention effect (8) further opens up the possibility of delivering chemotherapeutic drugs passively and more specifically to tumor sites, thereby limiting any damage to healthy tissues (9,10). A number of recent experimental (3,7,(11)(12)(13)(14)(15)(16)(17) and theoretical (18)(19)(20)(21)(22)(23) studies have suggested that particles of certain sizes and shapes have a higher margination propensity. This would facilitate the diffusion of these particles into tumor sites by allowing them to reach the leaky blood vessel walls and, ultimately, the tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to screening the interaction between tumor cells and nanoparticles, the transportation of nanoparticles in vessel tissues has been investigated to help create better nanoparticles. (75) Platforms for screening vascularization are still in the early stage of development. No long-term study of the formation of blood vessels has been carried out in microfluidic channels.…”
Section: Tumor-on-a-chipmentioning
confidence: 99%
“…Interestingly, the plasma skimming is recently revisited to develop new microchannels for detecting specific DNAs, proteins and cells by efficiently separating plasma from whole blood [9][10][11]. Also, it has been highlighted to accurately predict drug carrier distribution in the microvasculature [12][13][14][15][16][17][18]. For utilizing the plasma skimming to new applications in vitro and in vivo, it is crucial to quantitatively predict the redistribution of RBCs and plasma at bifurcations.…”
mentioning
confidence: 99%